Stress Cardiomyopathy Diagnosis and Treatment: JACC State-of-the-Art Review - de Chazal, Horacio Medina (J Am Coll Cardiol, 2018)
Stress cardiomyopathy is an acute reversible heart failure syndrome initially believed to represent a benign condition due to its self-limiting clinical course, but now recognized to be associated with a non-negligible rate of serious complications such as ventricular arrhythmias, systemic thromboembolism, and cardiogenic shock. Due to an increased awareness and recognition, the incidence of stress cardiomyopathy has been rising (15–30 cases per 100,000 per year), although the true incidence is unknown as the condition is likely underdiagnosed. Stress cardiomyopathy represents a form of neurocardiogenic myocardial stunning, and while the link between the brain and the heart is established, the exact pathophysiological mechanisms remain unclear. We herein review the proposed risk factors and triggers for the syndrome and discuss a practical approach to diagnosis and treatment of the patients with stress cardiomyopathy, highlighting potential challenges and unresolved questions.